2010
DOI: 10.1038/nature08828
|View full text |Cite
|
Sign up to set email alerts
|

Control of female gamete formation by a small RNA pathway in Arabidopsis

Abstract: In the ovules of most sexual flowering plants female gametogenesis is initiated from a single surviving gametic cell, the functional megaspore, formed after meiosis of the somatically derived megaspore mother cell (MMC)1,2. Because some mutants and certain sexual species exhibit more than one MMC2-4, and many others are able to form gametes without meiosis (by apomixis)5, it has been suggested that somatic cells in the ovule are competent to respond to a local signal likely to play an important function in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
574
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(615 citation statements)
references
References 33 publications
32
574
1
8
Order By: Relevance
“…It was shown that gamete formation requires AGO9, which controls female gamete formation in a non-cell autonomous manner (Olmedo-Monfil et al, 2010). In grafted Arabidopsis and Nicotiana the systemic silencing penetrated male sporogenic tissues suggesting that plants harbor an endogenous longdistance small RNA transport pathway facilitating siRNA signalling into meiotically active cells.…”
Section: Flower/seed Concerning Silencing Spreadingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that gamete formation requires AGO9, which controls female gamete formation in a non-cell autonomous manner (Olmedo-Monfil et al, 2010). In grafted Arabidopsis and Nicotiana the systemic silencing penetrated male sporogenic tissues suggesting that plants harbor an endogenous longdistance small RNA transport pathway facilitating siRNA signalling into meiotically active cells.…”
Section: Flower/seed Concerning Silencing Spreadingmentioning
confidence: 99%
“…AGO9 is involved in RNA-directed DNA methylation and is highly enriched in the germline (Oliver et al, 2014) where it controls female gamete formation by repressing the specification of germ cell fate through epigenetic reprogramming in companion somatic cells (Olmedo-Monfil et al, 2010). Zea mays AGO2 homolog (originally designated ZmAGO104) is also specifically expressed in the somatic cells surrounding future gametes but it had an opposing function -it suppresses the somatic cell fate in germ cells (Singh et al, 2011).…”
Section: Ago8 -Seems To Be a Pseudogene In A Thaliana (Zhang Et Almentioning
confidence: 99%
“…AGO9 is expressed in cytoplasmic foci of somatic companion cells. AGO9 preferentially interacts with 24-nucleotide siRNAs derived from TEs and silences TEs in female gamete and their accessory cells likely in a non-cell-autonomous manner, thereby repressing germ cell fate in somatic cells (Olmedo-Monfil et al, 2010). In maize, the AGO9 homolog (named AGO104) is specifically expressed in the somatic cells around the precursors of the gametic cells but acts to repress somatic fate in germ cells (Singh et al, 2011).…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Mutations in AGO9 lead to the differentiation of multiple female gamete precursors that are able to initiate gametogenesis and give rise to independent female gametophytes in the ovule, in a pattern reminiscent of aposporous apomixis (Olmedo-Monfil et al 2010). The AGO9 protein is not expressed in the gamete lineage; instead, it is expressed in somatic companion cells.…”
Section: Epigenetic Control Of Cell Specification In the Arabidopsismentioning
confidence: 99%